Molecular surveillance reveals a potential hotspot of tick-borne disease in Yakeshi City, Inner Mongolia - Junhua Tian; Jing Liu; Hongqing Zhao; Xiaomin Chen; Xueqin Geng; Miao Lu; Kun Li (BMC Microbiology, 2023)
Abstract A molecular surveillance of tick-borne diseases was performed in Hulunbuir City, Inner Mongolia. A total of 149 ticks including three species (Ixodes persulcatus, Haemaphysalis concinna, and Dermacentor silvarum) were collected. As many as 11 tick-borne bacterial pathogens were identified in them. Some of them have high positive rates. For example, Candidatus Rickettsia tarasevichiae was detected with a high prevalence of 72.48%, while Candidatus Lariskella sp. was detected in 31.54% of ticks. For both Rickettsia raoultii and Anaplasma phagocytophilum, two distinct genotypes were identified based on their phylogenetic trees based on 16S rRNA, gltA, and groEL sequences. Remarkable genetic diversity was also observed for 16S and flaB genes of Borreliella garinii, an agent of Lyme disease. Rickettsia heilongjiangensis causing Far-Eastern spotted fever (2.68%, 4/149), Ehrlichia muris causing human ehrlichiosis (4.70%, 7/149), Borrelia miyamotoi causing relapsing fever (2.01%, 3/149), and Borreliella afzelii causing Lyme disease (2.01%, 3/149) were also detected. Additionally, a previously uncharacterized Anaplasma species closely related to Anaplasma ovis was identified. Herein we name it “Candidatus Anaplasma mongolica”. Based on these results, we propose that Yakeshi City might be a potential hotspot of tick-borne diseases.